RESEARCH AND EDUCATION IN THE MEDICAL AREA - Vallejo, Msc. Alida; RAMIREZ-AMAYA, DRA. JOSEFINA; GUZMAN, JUANA KOU; TERAN, CESAR NOBOA; PALACIOS, OSWALDO ZAVALA; DURÁN-ÁVILA, NARCISA LILIANA (International Journal of Research -GRANTHAALAYAH, 2020)
The training of health professionals poses a great challenge in developing countries around the world. Medicine of the XXI century, represented in health careers, has a direct relationship with scientific and technical development, involves, observation, the search for knowledge about the problems that affect the health and biological well-being of the human being. This work implies a great ethical commitment to society, hence the importance of strengthening research capacity in both undergraduate and graduate studies. Developing human talent is a task that must be carried out continuously from the beginning of the medical career. Preserving life and preventing serious complications in the vulnerable population due to known or unknown pathologies is an unavoidable function of all health personnel, this is only achieved by training future professionals in the best way to guarantee the survival of future generations against the pathogenic microorganisms that can cause death. Teachers must implement the necessary strategies to motivate new professionals. Curiosity and interest must be strengthened throughout all medical careers.